Nonlinear dependence study of ionospheric F2 layer critical frequency with respect to the solar activity indices using the mutual information method. Issue 5 (1st September 2019) - Bai, Hongmei; Feng, Feng; Wang, Jian; Wu, Taosuo
Highlights: Mutual information is effective to analyze dependence of foF2 on R12 and F10.712 . Dependence of foF2 on R12 and F10.712 differ in different solar activity years. Mutual information provides an effective selection of inputs for foF2 prediction. Abstract: This paper analyzes the dependence of the ionospheric F2 layer critical frequency, f oF2, on two widely used solar activity indices (12-month running mean of the sunspot number (R12 ) and the solar radio flux of 10.7 cm wavelength (F10.712 )) by using mutual information method at the ionospheric station of Darwin (geographic 12.4°S, 131.5°E) in Australia. The results show that the f oF2 have different responses to R12 and F10.712 in different solar activity years. In the high and low solar activity years, the f oF2 is more dependent on R12 rather than F10.712 . In the moderate solar activity years, the f oF2 is more dependent on F10.712 rather than R12 . We further verify the effectiveness of the mutual information on the selection of the solar activity index by developing the prediction models of the f oF2. Additionally, the results are compared against the International Reference Ionosphere (IRI) model. The data of training period used in the model is from 1998 to 2015, except 2000, 2009 and 2013. Data for 2000, 2009 and 2013 are used to validate the prediction accuracy, for high, low and moderate solar activity years, respectively. The results demonstrate that the favorable prediction results can be obtained when the solar activity index with large mutual information is used as the input variable of the fo F2 prediction model. The proposed method not only can quantitatively analyze the nonlinear relationship between the fo F2 and solar activity indices but also provides an effective way of selecting the solar activity indices for the fo F2 prediction.